On one criterion of constancy of a complex function - Safonov, V. M.; Trohimchuk, Yu. Yu; Сафонов, В. М.; Трохимчук, Ю. Ю.; Сафонов, В. М.; Трохимчук, Ю. Ю. (Institute of Mathematics, NAS of Ukraine, 1999)
A new criterion of constancy of complex functions is proved.